Arteriovenous Fistula from the Left and Right Coronary Arteries -to- Pulmonary Artery Presenting with Acute Myocardial Infraction - Husain H. Jabbad, (Journal of King Abdulaziz University: Medical Sciences, 2023)
This is a review of a case study of a bilateral coronary artery fistulae originating from the left anterior descending artery, plus the right coronary artery to form a spiral shape arteriovenous malformation, and draining into the pulmonary artery. The patient presented with an acute coronary syndrome and a myocardial infarction due to a complete occlusion of the left anterior descending, distal to the origin of the fistula branches arising from the proximal left anterior descending. The left anterior descending was grafted with left internal mammary graft with surgical resection of the fistula; the post operative course was uneventful. After 2 years, the patient continues to be asymptomatic and was back to heavy work with no complaints.